A Pedigree Report of a Rare Case of Weill–Marchesani Syndrome with New Compound Heterozygous LTBP2 Mutations - Lin Z; Zhu M; Deng H (Dove Medical Press, 2021)
ZhiHong Lin,* MinJuan Zhu,* HongWei Deng Department of Strabismus & Pediatric Ophthalmology, Shenzhen Eye Hospital Affiliated to Jinan University, The School of Optometry of Shenzhen University, Shenzhen, 518000, Guangdong Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: HongWei DengDepartment of Strabismus & Pediatric Ophthalmology, Shenzhen Eye Hospital Affiliated to Jinan University, The School of Optometry of Shenzhen University, No. 18 of Zetian Street, Futian District, Shenzhen, 518000, People’s Republic of ChinaTel +86 0755 23959542Fax +86 0755 23959500Email denghwdr@21cn.comBackground: Weill–Marchesani syndrome (WMS) is an autosomal inherited connective tissue disease. Clinical manifestations include microspherophakia (MSP), high myopia, ectopia lentis, open-angle glaucoma, short stature, short fingers, joint stiffness, and (occasionally) cardiovascular defects. At present, a total of four pathogenic gene loci related to WMS have been found: ADAMTS10, ADAMTS17, FBN1, and LTBP2.Case Report: The patient was a five-year-old girl whose eyesight had become progressively worse for three years before her parents brought her to the hospital. Computer optometry showed high myopia in both eyes, while a slit lamp examination found that the anterior chamber of both eyes was shallow, and the lens was in a state of dislocation (ectopia lentis). An IOLMaster examination revealed that the lens was spherical (MSP), and the lens thickness (LT) was 5.36 mm. Corneal topography showed that the angle kappa was 0.18 mm in the right eye (OD) and 0.30 mm in the left eye (OS). An intraocular pressure (IOP) (OD: 26.5 mmHg, OS: 30.6 mmHg) examination showed that the fundus cup to disc ratio was normal, but secondary glaucoma caused by lens dislocation could be considered. The IOP was maintained within a normal range using antihypertensive drugs. The patient’s younger sister also had a dislocation of MSP. Gene detection showed a heterozygous mutation in the LTBP2 gene [c.3672delC:p.Thr1225fs and c.3542delT:p.Met1181fs], and a diagnosis of WMS-like syndrome was confirmed.Conclusion: WMS syndrome is rare, and the mutation of the LTBP2 gene has not been previously recorded in the GnomAD (Genome Aggregation Database) of East Asia. This case report provides some reference for studying the mechanism of WMS and WMS-like syndrome caused by an LTBP2 gene mutation.Keywords: Weill–Marchesani syndrome, microspherophakia, ectopia lentis, LTBP2, compound heterozygous, secondary glaucoma